Pulmonary hypertension in children with congenital heart disease (PAH-CHD, PPHVD-CHD). Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Kozlik-Feldmann, Rainer; Hansmann, Georg; Bonnet, Damien; Schranz, Dietmar; Apitz, Christian; Michel-Behnke, Ina
Abstract : Pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD) is a complex disease that presents with a broad spectrum of morphological and haemodynamic findings of varying severity. Recently, the aspect of paediatric pulmonary hypertensive vascular disease (PPHVD) has been introduced to expand the understanding of the full spectrum of pulmonary hypertension and increased pulmonary vascular resistance. Evaluation and treatment of PAH-CHD/PPHVD-CHD can be divided into in different topics. First, defining criteria for operability and initiation of advanced therapies preoperatively and postoperatively is an unresolved issue. Second, management of Eisenmenger syndrome is still an important question, with recent evidence on the severity of the disease and a more rapidly progressive course than previously described. Third, the Fontan circulation with no subpulmonary ventricle requires a distinct discussion, definition and classification since even a mild rise in pulmonary vascular resistance may lead to the so-called failing Fontan situation. Patients with CHD and single-ventricle physiology (Fontan/total cavopulmonary anastomosis) require a particularly stepwise and individualised approach. This consensus statement is on the current evidence for the most accurate evaluation and treatment of increased pulmonary artery pressure and resistance, as well as ventricular dysfunction, in children with congenital heart defects, and provides according practical recommendations. To optimise preoperative and postoperative management in patients with PAH-CHD, diagnostic and treatment algorithms are provided.